Regional Circular Economy Knowledge Hubs As Future Enablers Of The Green Transition In EGTC-Based Cross-Border Cooperation - Bódizs, Dalma (Sustainable Governance in the Age of Artificial Intelligence: Interdisciplinary Perspectives on ESG, Digital Transformation and Corporate Responsibility, 2026)
The European Union’s transition towards a circular economy necessitates profound technological, institutional, and societal transformations. Regional circular economy knowledge hubs are emerging as potential instruments to facilitate this transition, particularly within EGTC-based cross-border cooperation networks, although their practical implementation remains limited. This paper employs Multi-Level Perspective to explore the prospective role of such hubs, situating them within broader socio-technical landscapes, regional regimes, and niche innovations. Analysis suggests that knowledge hubs could enable the alignment of local competencies, industrial experimentation, and policy frameworks, fostering the development of resilient, regionally embedded circular economy models. By bridging emerging niche practices and established regional structures, these hubs may support the stabilization of sustainable innovations, enhance cross-border learning, and promote inclusive regional development. The research also identifies potential challenges, including institutional fragmentation, uneven resource distribution, and varying levels of stakeholder engagement, which could constrain their future effectiveness. Policy implications highlight the importance of strategically supporting experimental, multi-level initiatives, reinforcing the institutional embedding of knowledge hubs, and encouraging the replication and scaling of successful practices across regions. Although largely conceptual, regional circular economy knowledge hubs could represent a strategic pathway for advancing green transition, enhancing regional resilience, and promoting socially responsible, sustainable development across European territories.